2006
DOI: 10.1002/smi.1095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a firm purpose in life on anxiety and sympathetic nervous activity caused by emotional stress: assessment by psycho-physiological method

Abstract: Purpose: The concept of purpose in life (PIL) has been explained using such words as ‘existentialism’ or ‘meaning in life’. Crumbaugh and Maholic devised a method to quantitatively measure the meaning in life called the PIL test. To clarify the effect of emotional stress on health, the effects of PIL on anxiety and sympathetic nervous activity caused by emotional stress were assessed. Also the relationship between experiences in life and PIL in adults were examined. Methods: Thirty‐two healthy male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 9 publications
8
71
0
4
Order By: Relevance
“…LF/HF might have been influenced by psychological stress, which can independently affect LF and HF (31,33), and can cause both activation of sympathetic, and inhibition of vagal, activity (33). Negative stressors such as tension and fear (34), increased effort when conducting tasks (31), and a deficit in positive social relationships, or having negative social experiences despite making affiliative efforts, can all result in increased sympathetic activity, and potentially lead to greater LF and LF/HF (31,35). It may be possible, therefore, that children with poorer social relationships and greater psychological stress were more likely to have a higher LF/HF and gain more weight post-intervention for reasons linked, not only to their inhibitory capacity, but also to their psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…LF/HF might have been influenced by psychological stress, which can independently affect LF and HF (31,33), and can cause both activation of sympathetic, and inhibition of vagal, activity (33). Negative stressors such as tension and fear (34), increased effort when conducting tasks (31), and a deficit in positive social relationships, or having negative social experiences despite making affiliative efforts, can all result in increased sympathetic activity, and potentially lead to greater LF and LF/HF (31,35). It may be possible, therefore, that children with poorer social relationships and greater psychological stress were more likely to have a higher LF/HF and gain more weight post-intervention for reasons linked, not only to their inhibitory capacity, but also to their psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, higher baseline measures of purpose have been found to be negatively associated with mortality, dementia, and psychiatric and somatic symptoms (Boyle et al 2009(Boyle et al , 2010. Life purpose has also been found to reduce the risk of anxiety, depressive symptoms, stroke, and other cardiovascular events, and it can ease responses to emotional stress (Ishida and Okada 2006;Krause 2007). The search for meaning and life direction has been shown to act as a regulatory function of health that predicts healthy eating and activity among adolescent and adult populations (Brassai et al 2015;Piko and Brassai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed that PIL/ikigai is an effective way to cope with stress. More specifically, persons with firm PIL/ikigai can better decrease anxiety, mental and somatic subjective symptoms and increase pleasure and comfort even in stressful situations and society compared with persons with weak PIL/ikigai [25]. Furthermore, persons with PIL/ikigai have distinct personality traits: having lower social desirability, which is an attitude based on the need for approval and an attempt to adapt excessively to expectation of their society; attaining their purpose with enthusiasm and patience and without impulse; respecting the personality of other persons; and having an more independent spirit [3,21,26,27].…”
Section: Purpose In Life (Pil)/ikigaimentioning
confidence: 99%